Potential of carbon sequestration enhancement through intensive silvicultural techniques using Shorea leprosula plantation in Central Kalimantan, Indonesia - M. ISKANDAR; ISKANDAR ZULKARNAEN SIREGAR; HARUNI KRISNAWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Iskandar M, Siregar IZ, Krisnawati H. 2023. Potential of carbon sequestration enhancement through intensive silvicultural techniques using Shorea leprosula plantation in Central Kalimantan, Indonesia. Biodiversitas 24: 4699-4713. Various sectors are involved in achieving Indonesia’s Enhanced Nationally Determined Contribution (NDC), including Forestry and Other Land Uses (FOLU) sector. Sustainable Forest Management (SFM) implementation by forest concessionaires (PBPHs) enormously contributes to land-based mitigation activities, primarily at the local level. One of the SFM activities is forest enrichment with Intensive Silvicultural (SILIN) technique using Shorea leprosula Miq. to enhance carbon stock and sequestration. This study was conducted in PT Sarmiento Parakantja Timber (PT Sarpatim) in Central Kalimantan (Indonesia) and used the measurement data from 32 purposive sampling plots. Each plot was 40m × 40m in size, constructed under three different SILIN patterns (conventional strip, effective strip, and gap) as well as natural forest stands. This study found that SILIN gap pattern had higher carbon stock and sequestration potential, compared to the natural forest (reference) stands, and reached a net sink condition after 30 years. For the stands of SILIN conventional and effective strip patterns, the carbon stocks were lower than the reference stand, even when the vegetation aged 30 years. PBPHs applying SILIN technique as part of the SFM and the mitigation actions demonstrate an enhanced carbon stock and sequestration. This effort supports Indonesia’s Enhanced NDC target and FOLU Net Sink 2030.